Exploiting beacon's size for scalable junction-based routing in city scenarios of VANETs. (5th July 2021) - Zahedi, Khalid; Ismail, Abdul Samad; Zahedi, Yasser
This work presents a new routing protocol designed exclusively for improving the scalability of junction-based routing in city scenarios of vehicular ad hoc networks (VANETs). The main characteristic of the proposed protocol is reducing the total generated beacon overhead by decreasing the size of the periodically exchanged beacons instead of their number. In particular, the proposed protocol exploits the received power of the neighbouring nodes (instead of their positions) to determine the nearest neighbour to the destination. Thus, makes it possible to decrease the size of beacon by removing the position information field. Results have shown a decrease in both control and beacon overheads of the proposed protocol in comparison to other junction-based protocols.